A case study on a selected tambayan in the University of the Philippines in relation to the sense of place of its users - Celadeña, Allyson Joyce D. (College of Home Economics, University of the Philippines Diliman, 2019)
The study determined a selected tambayan's relation to the sense of place of its users using four main concepts from Steele's (1981) theory of sense of place. It examined two main elements of the tambayan, the interior and its users, and then explained the relationship between the two elements in forming a sense of place with the tambayan. Purposive sampling was used to choose the tambayan, taking into account the organization's age, members, floor area, and frequency of use. Nine respondents were chosen to participate in the study, equally distributed under regular, honorary, and alumni member categories that helped give different perspectives about the sense of place in the tambayan. Two weeks were spent on the data collection using tools such as ocular observation, photo documentation, interviews, and survey questionnaires. The study showed that in the chosen tamabayan, all four concepts of sense of place were present in terms of physical and experiential space, as well as to its users; therefore proving the existence of sense of place in the tambayan. It was the presence of the community in the tambayan that most affected the sense of place of its users. Furthermore, it was also discovered that the users had a deeper connection to the place. called spirit of place, where users create a feel of personality to the space brought about by the combination of interior elements (Steele, 1981). Finally, the researcher recommend improvements in the interior design of the tambayan, a more extensive study about sense of place in tambayans in different settings and generations, and the application of sense of place in the campus environment as a whole.